OPTIMIZATION OF SOLAR-WIND-DIESEL HYBRID POWER SYSTEM DESIGN USING HOMER - Ignatius Agung Wibowo; Darwin Sebayang (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2015)
Indonesia has a lot of potential for renewable energy. Electricity generation from hybrid solar and wind energy will be a prospective solution to fulfill electricity supply for remote and rural communities. Although diesel generator was still part of the hybrid power system, however, with a proper design, the fuel consumption could be reduced significantly. HOMER software was utilized to aid the design process by providing optimum configuration of the hybrid power system components in terms of performance and economy.